Hand-portable HPLC with broadband spectral detection enables analysis of complex polycyclic aromatic hydrocarbon mixtures - Stelios Chatzimichail; Faraz Rahimi; Aliyah Saifuddin; Andrew J. Surman; Simon D. Taylor-Robinson; Ali Salehi-Reyhani (Communications Chemistry, 2021)
Portable liquid chromatography instruments enable a myriad of applications in field research. Here a handportable system incorporating a broadband absorption detector is used to separate and classify polycyclic aromatic hydrocarbons from environmental water samples based solely on spectral fingerprinting.